#### Answer

$f'(x)=\frac{-27}{x^{10}}$

#### Work Step by Step

$f(x) = 3x^{-9}$
Power rule: $f'(x) = 3(-9)x^{(-9-1)} = \frac{-27}{x^{10}}$

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

$f'(x)=\frac{-27}{x^{10}}$

$f(x) = 3x^{-9}$
Power rule: $f'(x) = 3(-9)x^{(-9-1)} = \frac{-27}{x^{10}}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.